Multikulturalizm – analiza krytyczna - Ryba, Mieczysław (Społeczeństwo, 2022)
The ideology of multiculturalism has recently become dominant in the Western world. This applies not only to America, but especially to Western Europe. It has its roots in the neo- Marxist philosophy of the Frankfurt School. The implementation of the multicultural world project is closely connected with the policy of „open doors”, ie the political plan of huge immigration of people from cultures and civilizations that are far from the Western world. The ruthless implementation of this project, however, encounters increasing resistance, associated with the explosion of a huge number of conflicts (example: terrorist attacks), by some called the „war of civilization”. A further consequence of this type of process is the emergence of increasingly strong „anti-system” groups on the political market, undermining the unification processes in the Western world.